ERRORS IN THE CLASSROOM: DILEMMAS AND PRACTICES - Taslimah Retno Marpinjun (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
Human learning is fundamentally a process that involves the making of errors. But the issue of error and how errors are treated in the classroom is still dilemma for many teachers.  One learning approach stated that error correction was avoided, because it makes learners shut off their attempts at communication. However, other learning approaches stated that correction was highly valued, to increase students’ motivation in learning. For the best decision, teacher can use  five key questions dealing with errors’ treatment: (1) should learners’  errors be corrected ?; (2) when should learners’ errors be corrected?; (3) which errors should be corrected?; (4) how should learners’ errors be corrected; and (5) who should do the correcting?